Physically Based Summer Temperature Reconstruction From Melt Layers in Ice Cores. Issue 7 (9th July 2021) - Fujita, Koji; Matoba, Sumito; Iizuka, Yoshinori; Takeuchi, Nozomu; Tsushima, Akane; Kurosaki, Yutaka; Aoki, Teruo
Abstract: Previous reconstructions of summer temperatures from ice cores have relied on a statistical relationship between a melt layer and temperature observed at nearby stations. This study presents a novel method for reconstructing summer temperatures from melt layers in ice cores using an energy balance model that incorporates heat conduction and meltwater refreezing in the firn. We use the seasonal patterns in the ERA‐Interim reanalysis data set for an ice core site to calculate the amounts of refreezing water within the firn under various summer mean temperature (SMT) and annual precipitation conditions, and prepared calibration tables containing these three variables. We then estimate the SMTs from the refreezing amount and annual accumulation, both of which can be obtained from an ice core. We apply this method to four ice cores that were recovered from sites with different climates: two sites on the Greenland Ice Sheet, one in Alaska, and one in Russian Altai. The reconstructed SMTs show comparable variations with those of observed temperatures at nearby stations. The nonlinear relationship between SMT and melt layer thickness differs between sites, indicating that a single linear approximation cannot be employed to estimate SMT. Sensitivity analyses suggest that the annual temperature range, amount of annual precipitation, and firn albedo (which is a time‐invariant value in the model) significantly affect the relationship between SMT and melt layer thickness. This new method provides an alternative to existing approaches and yields an independent estimate of SMT from ice cores that have been affected by melting. Plain Language Summary: Melt layers in ice cores have been widely used as a proxy for summer temperatures. Previous studies established a statistical relationship between melt layer thickness and temperature observed at nearby stations and then applied it to the deeper part of the ice core. This study presents a novel method for reconstructing summer temperatures from the melt layer thickness in an ice core using an energy balance model that incorporates heat conduction and meltwater refreezing in the firn. We calculate the refreezing amounts within the firn under various summer mean temperature (SMT) and annual precipitation conditions, for which a reanalysis data set is systematically changed. We then estimate the SMTs from the refreezing amount (estimated from melt layer thickness) and annual accumulation, both of which can be obtained from an ice core. We apply this method to four ice cores recovered from different climatic sites. The reconstructed SMTs show comparable variations with those of observed temperatures at nearby stations. The relationship between SMT and melt layer thickness differs between sites, indicating that a single approximation cannot be employed to estimate SMT. This new method provides an alternative independent estimate of SMT from ice cores affected by melting. Key Points: A novel method to reconstruct summer temperatures from melt layers by a numerical model is developed and applied to four ice cores Nonlinear relations between summer temperature and melt layer thickness suggest that a traditional linear approximation is not applicable Relation between summer temperature and melt layer thickness is affected by annual temperature range, annual precipitation and firn albedo